Technical expert CEOs and corporate innovation - Ting,Hsiu-I; Wang,Ming-Chun; Yang,Jimmy; Tuan,Kai-Wen (Pacific-Basin Finance Journal, 2021)
Keywords: Finance

Trader Positions in VIX Futures - Chen,Yu-Lun; Yang,Jimmy (Journal of Empirical Finance, 2021)
We investigate the dynamic changes in trader positions of market participants in the VIX futures markets. We find that in a low-VIX period, below the 23.81 threshold determined by our model, changes in VIX futures affect the trading decisions of dealers and leveraged fund managers, but in an opposite direction. During a high-VIX period, dealers and leveraged fund managers would then alter their trading strategies. We highlight the important role of exchange-traded products trading in hedging demand of dealers and show the impact on VIX futures. Trader positions are determinants of VIX futures prices, basis, and VIX premium.
Keywords: Finance

Trading activity and price discovery in Bitcoin futures markets - Hung,Jui-Cheng; Liu,Hung-Chun; Yang,Jimmy (Journal of Empirical Finance, 2021)
Keywords: Finance

Teaching an Old Dog New Tricks: Using the Dividend Growth Model in Financial Planning - Brooks,Raymond; Yang,Jimmy (Journal of Economics and Finance Education, 2007)
The Dividend Growth Model is a standard pedagogical tool in pricing stocks where the dividend grows at a constant rate. However, few dividend policies conform to this restrictive pattern and therefore the model is often quickly discarded in finance classes. The constant growth assumption of a cash flow stream fits well with other financial problems such as saving for a college education or contributions to a pension plan. This paper presents a couple of applications for the Dividend Growth Model plus an extension to the model and belies the adage: you can’t teach an old dog new tricks.
Keywords: Finance